Economic growth in Australia: globalisation, trade and foreign direct investment. (1st January 2014) - Thorpe, Michael; Leitão, Nuno Carlos
Economic growth in Australia has outperformed that in most other OECD countries over the past couple of decades. This paper investigates the factors contributing to economic growth in Australia over the period 1986–2007. Particular focus is placed on the impact of external linkages. A major objective is to incorporate explanatory variables based on Dreher (2006) which capture different dimensions of globalisation; an overall index of globalisation is used along with sub-indices reflecting economic, social and political influences. A dynamic panel data approach (GMM-System) is employed.